TEACHING-SERVICE-COMMUNITY INTEGRATION-SUCH AS THE PET SAÚDE EQUITY PROGRAM BRINGS UNIVERSITY AND SUS. (CIPEEX, 2025)
Introduction: Strengthening the Unified Health System (SUS) depends on the training of professionals committed to social reality and prepared to work in various contexts. PET-Health Equity promotes the integration between teaching, service and community, bringing the University of Health Services and the needs of the population closer. Objective: Analyzing how the PET-Health Program contributes to the approach between university and SUS, strengthening focus practices with equity. Methods: It is an experience of teaching-service-community integration, in which students and preceptors develop activities together through educational actions, Services, conversation wheels and intervention projects. Results: Participation in the program enabled greater understanding of social health determinants, development of interprofessional practices, strengthening the bond with the community and production of strategies aimed at reducing health inequalities. Conclusion: PET-health was an important instrument to integrate academic background with the demands of SUS, promoting significant learning for students, qualification of services, qualification of services, services Health and advances in promoting health equity.